Hysteroid fungi (Dothideomycetes, Ascomycota) of the tropical dry forest in the National Park Lagunas de Chacahua, Oaxaca, Mexico - Álvarez, Víctor I.; Raymundo, Tania; Valenzuela, Ricardo (Instituto de Ecología, A.C., 2016)
Four species of hysterioid fungi belonging to the class Dothideomycetes of the phylum Ascomycota occurring in the tropical dry forest in the National Park of “Lagunas de Chacahua” in the state of Oaxaca are described and illustrated. Of these, Anteaglonium abbreviatum and Rhytidhysteron rufulum are new records for the state, Psiloglonium simulans is cited for the first time for Mexico and Gloniella tropicalis is described as a species new to science.